KEBIJAKAN MAKAN BERGIZI GRATIS DI INDONESIA: ANALISIS IMPLEMENTASI, DAMPAK TERHADAP SUMBER DAYA MANUSIA, DAN IMPLIKASINYA PADA KEBIJAKAN SISTEM PENDIDIKAN NASIONAL - Fatimah Yuliani; Winda Juniarsih; Harun Joko Prayitno; Indri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Free Nutritious Meals (MBG) policy launched by the Indonesian government in early 2025 is one of the strategic programs in the National Medium-Term Development Plan (RPJMN) 2025–2029. This program aims to improve the nutritional status of school-age children, pregnant women, and toddlers as a long-term investment in the development of quality human resources. This article examines the implementation of the MBG policy using a public policy analysis approach with a systematic literature review method. Data were collected from various scientific journals, government reports, and policy documents published between 2021 and 2026. The results of the study show that the MBG program has significant potential in improving student learning achievement and concentration, reducing stunting rates, and encouraging local economic growth through the involvement of SMEs and local farmers. However, the implementation of this program faces various challenges, including limited distribution infrastructure, regional capacity gaps, potential budget leakage, and lack of cross-sector coordination. Policy implications from these findings include the need for strengthened governance, development of program management human resources, and integration of MBG within a comprehensive national education system policy framework. This research confirms that the success of MBG is highly dependent on synergy between the central government, regional governments, the private sector, and the community in a holistic educational ecosystem.